A Participatory Model for Assisting with Ablution Practices in Strengthening Community Worship - Qurrotul Ainiyah; Dita Dzata Mirrota; Moch. Sya’roni Hasan; Mar’atul Azizah; Muhammad Anas Ma’arif; Humairourrohmah binti Mastor (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2026)
This community service program aims to improve mothers’ understanding and practical skills in performing proper ablution (wudhu) in Wonotirto Hamlet, Wonomerto Village, Wonosalam District, Jombang Regency. The program was initiated based on preliminary findings indicating that some mothers practiced ablution in ways that did not fully comply with its pillars and legal requirements, particularly regarding the sequence and completeness of washing the required body parts. Such practices potentially affect the validity of daily prayer performance. The community service activity was conducted using a practice-based mentoring approach that integrated the delivery of basic materials, interactive dialogue, demonstrations, and guided individual practice. This approach was selected to provide an applicable and contextual learning experience suitable for participants of diverse ages and religious educational backgrounds. Data were collected through observation, question-and-answer sessions, and activity documentation. The results of the program indicate an improvement in participants’ understanding of the basic concepts of ablution, its pillars and legal requirements, as well as actions that invalidate or perfect ablution. In addition, participants’ practical skills in performing ablution showed significant improvement, as evidenced by a more orderly sequence and more complete washing of the required body parts. The activity also increased participants’ awareness and motivation to improve the quality of their worship and their readiness to transfer proper ablution practices to family members. Therefore, this practice-based ablution mentoring program contributes to strengthening the quality of community worship and may serve as an applicable and sustainable model for community service in religious practice development